Biomarkers and trace elements in beta thalassemia major - Khaleel, Khaleed Jumaa (Iraqi Journal of Cancer and Medical Genetics, 2013)
Introduction: Beta thalassemia is one of the most common inherited single gene disorders result from absent or reduced β - chain production. Regular blood transfusions are required to correct anemia for normal growth and development, this cause secondary iron overload which is responsible for peroxidative damage. Iron overload causes high concentrations of serum ferritin which is a protein that plays a key role in iron metabolism by binding and storing excess iron within cells. In β-thalassemia major, liver damage accounts for the changes in lipid profile including total-cholesterol (TC), high-density lipoprotein cholesterol (HDL-C) and triglyceride (TGL). Trace elements including zinc (Zn), copper (Cu) and magnesium (Mg) play a vital role in the body to perform its functions properly and should present in the body in appropriate amounts and must be available for reacting with other elements to form critical molecules as well as to participate in various important chemical reactions. The aims: to evaluate serum ferritin and trace elements (Copper, zinc and magnesium) and lipid profile in beta thalassemia major patients. Patients, material and methods: Patients: sixty patients were diagnosed as beta thalassemia major, they were on blood transfusion program, and thirty healthy medication free volunteers matched for age and sex were studied as control .Blood samples were taken after an overnight fast (12-14-hours.) and serum was obtained for estimation of ferritin levels by ELISA and for TC and TG that were determined enzymatically. The HDL-C was measured after precipitation of other lipoproteins .Copper; zinc and magnesium were estimated by Atomic Absorption Spectrophotometer. Results: A high ferritin level (747.55 ± 158.62 mg/l) was observed. The serum cholesterol and high density lipoprotein levels were found to be lower than normal control (94.4±7.48 and 40.83±4.64 mg/dl respectively), while serum triglyceride level was significantly higher than normal control (177.83±15.91). There was no correlation between serum ferittin and any of the studied lipids. Serum Copper and magnesium levels were significantly higher than normal control (152±6.4 mg/dl and 2.28±0.17 mg/dl respectively), while Serum zincs levels were significantly lower than normal (67.55±2.7 mg/dl) In conclusion : assessment of serum ferittin , trace elements and lipid profile in patients with beta thalassemia major revealed different levels in different studies suggesting variation in the factors influencing their levels in each patients and could be useful in follow up patients with beta thalassemia major.